Need for information in a representative sample of outpatients with schizophrenia disorders. (August 2018) - Andrade, Mário César Rezende; Slade, Mike; Bandeira, Marina; Evans-Lacko, Sara; Martin, Denise; Andreoli, Sérgio Baxter
Background: Providing adequate information and involving patients in treatment have become an essential component of mental health care. Despite this, research regarding the extent to which this need has been met in clinical services is still scarce. Aims: To investigate the need for information about psychiatric condition and treatment among outpatients with schizophrenia disorders and how this need is associated with service use, adjusting for sociodemographic and clinical characteristics. Methods: Need for information about condition and treatment, using the corresponding domain in the Camberwell Assessment of Need (CAN), in a representative sample of 401 schizophrenia outpatients in Santos, Brazil was assessed. Hierarchical logistic regression was used to investigate the association of information as a reported need and as an unmet need with service use variables, adjusting for sociodemographic and clinical characteristics. Results: Need for information was reported by 214 (53.4%) patients, being met in 101 (25.2%) and unmet in 113 (28.2%). Hierarchical regression indicated a significant association of a reported need with higher age of onset, family monitoring medication use last year and lower education level, which was only associated with an unmet need. Conclusion: Information was a commonly reported need and which was often unmet, showing no significant association with service use. Greater attention should be given by mental health services to information provision.